Circulating Human Neonatal Naïve B Cells are Deficient in CD73 Impairing Purine Salvage - Pettengill, Matthew Aaron; Levy, Ofer (Frontiers in Immunology, 2016)
Background Extracellular purines, in particular adenosine (Ado) and adenosine-triphosphate, are critical immunoregulatory molecules. Expression and activity of purine ecto-enzymes on B cells in neonatal and adult blood may influence their function and has been incompletely characterized. Methods Mononuclear cells were isolated from human neonatal (cord blood) or adult (peripheral blood) subjects and evaluated directly by flow cytometry for expression of purine ecto-enzymes. Additionally, B cell subsets were isolated from mononuclear cell fractions by fluorescence-activated cell sorting and gene transcription of purine ecto-enzymes (CD39 and CD73), Ado deaminase (ADA1), purine nucleoside phosphorylase, and select purine receptors (A2a) were evaluated by reverse transcription followed by qRT-PCR. Immuno-magnetic-bead isolated naïve B cells were evaluated for enzymatic activity by incubation with radio-labeled purines followed by thin-layer chromatography, and subsequent B cell Ado acquisition was evaluated by liquid scintillation quantitation of radio-labeled Ado uptake. Results Relative to their adult counterparts, neonatal circulating naïve B cells were markedly and selectively deficient in CD73 as observed by gene transcription, surface protein expression, and enzyme activity. Neonatal naïve B cell deficiency of CD73 expression significantly impaired their capacity to acquire extracellular purines for purine salvage. Conclusion Human neonatal circulating naïve B cells are selectively deficient in CD73, impairing extracellular purine acquisition and potentially contributing to impaired B cell responses in early life.